The effects of toilet training on development of adaptive behaviour among preschool children - Nurul Fathini Mohd Nawawi; Abdul Rahman Ahmad Badayai (Penerbit Universiti Kebangsaan Malaysia, 2021)
Toilet training is important for children's development so that they are always in a comfortable, dry and clean state. Educating children to urinate and defecate becomes effective if training is done early. This study used a quasi-experimental design. A total of 60 respondents consisted of two groups 30 children received toilet training and 30 children did not receive toilet training among parents and preschool children at Persatuan Tadika Islam Malaysia. The results of the study found that there was a significant difference between parents' knowledge of children's toilet training and there was a significant difference between toilet training on the adaptive behaviour developments of preschool children. The results of this study explained the effect of toilet training on the development of adaptive behaviour of preschool children as well as differences in the level of knowledge of parents about toilet training on children's toilet training practices. This study adds to the theoretical findings on the influence of parental behaviour on child development in describing in detail and better about the level of parental knowledge of toilet training and the development of adaptive behaviour of children. Parents especially need to know critically about children's developmental needs better and support from the Department of Islamic Development Malaysia can help prospective couples to gain knowledge of parenting through marriage courses conducted.